Icatibant for Angiotensin-Converting Enzyme Inhibitor-Induced Angioedema in Intubated Patients: Case Series and Literature Review - Erin K. Yeung; Haritha Saikumar; Jose Castaneda-Nerio; Sandra G. Adams; Mark Wong (Case Reports in Critical Care)
Purpose. A case series of icatibant use in intubated patients with angiotensin-converting enzyme inhibitor- (ACEI-) induced angioedema is presented along with a relevant literature review and recommendations for utilization. Summary. Three intubated patients admitted to the intensive care unit for ACEI-induced angioedema were treated with icatibant. A literature search identified one controlled study and four case reports describing the use of icatibant in intubated ACEI-induced angioedema patients. Conclusion. Icatibant administration in intubated patients may be beneficial in decreasing time to extubation and length of intensive care unit stay. In the three cases described, icatibant administration did not appear to elicit a response in intubated patients, which has been described in previous case reports. For clinicians considering icatibant in the treatment of ACEI-induced angioedema, earlier administration upon arrival to the ED or immediately upon arriving to the intensive care unit is strongly advised. The suggested benefit of icatibant in intubated ACEI-induced angioedema patients should be verified by randomized clinical trials and cost-benefit analyses should be performed at individual institutions.